The impact of freezing on the post-mortem human microbiome - Ogbanga, Nengi; Nelson, Andrew; Gino, Sarah; Wescott, Daniel J.; Mickleburgh, Hayley L.; Gocha, Timothy P.; Procopio, Noemi (Frontiers in Ecology and Evolution, 2023)
Human donations are often used in forensic research as they can provide unique insights into post-mortem research that cannot be obtained with animal proxies. This is especially true for forensic microbiome research, as human circumstances such as drug-use or health conditions may influence the post-mortem microbiome. However, it is not always feasible to conduct such research immediately after death. Donors are often stored frozen in human taphonomy facilities, pending the start of any experimental study, yet little is known about how freezing may affect their microbiome. We assessed the effects of freezing on the post-mortem human microbiome by analysing the microbial diversity and abundance of seven human donors at the Forensic Anthropology Center at Texas State (FACTS) before and after freezing. Swab samples were taken from five locations on each corpse upon arrival to FACTS and again after they had been frozen in storage for a period ranging between 11 and 40 days and subsequently thawed. After performing the microbiome analysis of the swabs via 16S rRNA gene metabarcoding, we found changes in the abundance levels of Proteobacteria, Bacteroidota and Firmicutes, as well as the presence of the new phyla Deinococcota and Myxococcota after freezing. However, none of these changes were significant when comparing community diversity before and after freezing. Our results show therefore that freezing does not significantly alter the human microbiome, and that frozen donors are suitable for forensic studies on the human thanatomicrobiome.